The population of damselflies (Agriocnemis sp.) during growing phase of paddy at Kawasan Sawah Tengah Padang, Merlimau Melaka / Syaza Izzati Mat Sod - Mat Sod, Syaza Izzati (Faculty of Plantation and Agrotechnology, 2019)
This study was aimed to study relationship between populations of Damselflies (Agriocnemis sp.) in growing phase of paddy by weekly and its relation with the diversity of alternate host plant in paddy farming surrounding area. This study was conducted in paddy field at Kawasan Sawah Tengah Padang, Merlimau, Melaka. The samplings visits were made starting from the 20th July until 11th September 2018 was covered 10 weeks of data collections periods. One sampling method is used which is yellow sticky trap and set up randomly in field. Only one species that was recorded which damselflies (Agriocnemis sp.) order of Odonata. A few of species host plant also recorded comprising Perennial Water Primrose (Ludwigia perennis L. Onagraceae), Jungle rice (Echinochloa colona), Fringe-rush (Fimbristylis dichotoma), Shrubby False Buttonweed (Spermacoce verticillata), Pill-Bearing Spurge (Euphorbia Hirta syn. E. pilulifera), Airport grass (Chloris barbata Sw), Rumput Minyak (Panicum milliforme) and Broadleaved Bristle Grass (Setarid palmifolia). Results indicated that the population of Damselflies (Agriocnemis sp.) by weekly during the growing phase of paddy has no significance since (p>0.05). Meanwhile, there is no significance relationship between the numbers of population damselflies with the diversity of host in paddy farming surrounding area. As a result, farmer should ensure a good balance between the populations of damselflies and insect pest also host plant as unwanted weed during the various phases of paddy development without any appreciable loss in yield. An effective way is crucial to conserve, use and enhance biodiversity for sustainable food security.